The monuments of the ‘old-order’ era in Jakarta: visual representation of Sukarno’s nationalism / Toto Sugiarto Arifin - Arifin, Toto Sugiarto (Universiti Teknologi MARA, 2016)
The construction of monuments in the ‘Old-Order’ (Orde Lama) era in Jakarta is an integral part of the Indonesian’s struggle. This study is a qualitative study with qualitative descriptive analysis through textual and contextual analysis focused on the spirit and the visual representation of the five monuments which were built during the reign of the Old-Order in Jakarta. These monuments are Monumen Selamat Datang, Pembebasan Irian Barat, Dirgantara, and Monumen Nasional (Monas). Monuments built in the Old-Order era in Jakarta, served as the representation of Nationalism from the first President of The Republic of Indonesia, Ir. Soekarno or better known to the Indonesian people as ‘Bung Karno’ that are reflected in the construction of monuments in his reign. These monuments are not portrayed as character, class, or certain ideology, but more as the representation of the life spirit from the Indonesian people and the values of their culture, depicted by Monumen Nasional as the center point of the four other monuments. Bung Karno is a consistent leader with strong character and has ability to integrate varieties of ethnic, class, religion, and ideology into one nationality. All of these are reflected in his ideas to build the five monuments, so that Bung Karno’s figure can be seen as a role model for leadership in Indonesia.